(untitled) (Journal of the College of Basic Education, 2023)
Theater is a collective act in which the author, director, actor, musician and designer participate.The viewer, the lighting engineer, and others in the making of his harmonious plexus dimensions of collective creativityEven when the writer is alone with himself and undertakes the first adventure of experimentation alone with his or her insomnia, heBearing in mind that the experimental act that produces its first strings is an act that embodieswith a random group. As a dramatic event, the antithesis of submissive stillness and servile silence.This collective dimension of theatrical experimentation establishes its presence in a causal relationship with the conditions ofmore complex than it is in the novel and poetry, where the individuality of creativity and reception differs fromThe collective formula necessary for theatrical activity.Through an aesthetic vision as one of the acts of experimentation that replaces the logic of rhythm and replacesThe place of creativity and the open horizon of the theatrical action is replaced by the strict rationality and the Baudip.Oedipus, mired in his complex, is the vital symbol of his subconscious creative impulse and rebellion againstEvery prison and knot.